The effect of the reciprocal teaching-learning model on the mathematical representation ability of eighth grade students viewed from self-esteem - Elis Fitriani; Zuida Ratih Hendrastuti; Yesi Franita (Universitas Sarjanawiyata Tamansiswa, 2025)
Effective mathematical representation is a fundamental component of mathematical problem-solving; however, many students experience persistent difficulties in developing this ability. This study aims to (1) examine differences in students’ mathematical representation abilities between those taught using the reciprocal teaching–learning model and those taught through direct instruction, (2) compare mathematical representation abilities among students with high, medium, and low self-esteem, and (3) investigate the interaction between learning model and self-esteem. This study employed a quantitative approach with a quasi-experimental design using a nonequivalent posttest-only control group. The experimental class consisted of 5 students with high self-esteem, 24 with medium self-esteem, and 3 with low self-esteem, while the control class included 6, 20, and 6 students in the respective categories. Data were analyzed using a two-way ANOVA. The results indicate that (1) students taught through the reciprocal teaching–learning model demonstrated significantly higher mathematical representation abilities than those taught using direct instruction, (2) mathematical representation abilities differed significantly across levels of self-esteem, and (3) there was no significant interaction between the learning model and self-esteem. In conclusion, the reciprocal teaching–learning model is more effective than direct instruction in enhancing students’ mathematical representation abilities, regardless of their self-esteem levels. The contribution of this study lies in providing empirical evidence that reciprocal teaching–learning can serve as an effective instructional model for strengthening mathematical representation skills while clarifying the independent role of self-esteem as an affective factor in mathematics learning.